JASMINE: Near-infrared astrometry and time-series photometry science - Kawata, Daisuke; Kawahara, Hajime; Gouda, Naoteru; Secrest, Nathan J; Kano, Ryouhei; Kataza, Hirokazu; Isobe, Naoki; Ohsawa, Ryou; Usui, Fumihiko; Yamada, Yoshiyuki; Graham, Alister W; Pettitt, Alex R; et al. (Publications of the Astronomical Society of Japan, 2024)
The Japan Astrometry Satellite Mission for INfrared Exploration (JASMINE) is a planned M-class science space mission by the Institute of Space and Astronautical Science, the Japan Aerospace Exploration Agency. JASMINE has two main science goals. One is Galactic archaeology with a Galactic Center survey, which aims to reveal the Milky Way’s central core structure and formation history from Gaia-level (∼25 ${μ} $as) astrometry in the near-infrared (NIR) Hw band (1.0-1.6 ${μ} $m). The other is an exoplanet survey, which aims to discover transiting Earth-like exoplanets in the habitable zone from NIR time-series photometry of M dwarfs when the Galactic Center is not accessible. We introduce the mission, review many science objectives, and present the instrument concept. JASMINE will be the first dedicated NIR astrometry space mission and provide precise astrometric information on the stars in the Galactic Center, taking advantage of the significantly lower extinction in the NIR. The precise astrometry is obtained by taking many short-exposure images. Hence, the JASMINE Galactic Center survey data will be valuable for studies of exoplanet transits, asteroseismology, variable stars, and microlensing studies, including discovery of (intermediate-mass) black holes. We highlight a swath of such potential science, and also describe synergies with other missions.
Online veröffentlicht: 10. April 2024
Gesehen am 13.11.2024